A mixed phase lanthanum vanadate in situ induced by graphene oxide/graphite carbon nitride for efficient photocatalytic hydrogen generation. (5th August 2021) - Zhou, Yuzhi; Zhang, Linxia; Qin, Lixia; Kang, Shi-Zhao; Li, Xiangqing
Abstract: A mixed phase LaVO4 with high dispersion was in situ induced and implanted in graphene oxide-graphite carbon nitride composite. The obtained nanocomposite (GO–C3 N4 –LaVO4 ) showed high and stable photocatalytic activity for hydrogen evolution, which significantly benefited from the improved charge separation and light absorption in the special composite photocatalyst as evidenced by UV–vis spectra, fluorescence spectrum, photocurrent response and electrochemical impedance. The fabrication strategy of mixed phase LaVO4 in the GO-C3 N4 provides a new idea for constructing cheap and active organic-inorganic semiconductor photocatalysts for hydrogen generation. Graphical abstract: Image 1 Highlights: A LaVO4 with mixed phase was facilely in-situ implanted in the GO-C3 N4 . Charge separation can be greatly enhanced in the obtained nanocomposite. The mechanisms of fabrication and charge transfer in the composite were explored. The nanocomposite exhibited excellent photocatalytic performance for H2 production.